PENINGKATAN KETERAMPILAN BERBICARA MELALUI MEDIA WAYANG BERBASIS BUDAYA LOKAL PADA MATERI BERCERITA DI KELAS IV UPT SD NEGERI 100 GRESIK - Siti Fatimah Abdilah; Nanang Khoirul Umam (Universitas Muhammadiyah Gresik, 2020)
This research aims to improve the speaking skills through local culture based puppet media on storytelling in class IV of UPT SD Negeri 100 Gresik in the academic year 2019-2020. This research is a (Classroom Action Research) conducted collaboratively with class teachers. The design of this study uses the Arifin’s model which consists of 4 stages namely planning, implementation, observation, and reflection. Research subjects were 18 of students. Data collection techniques used are in the form of tests, while research instruments use test sheets to find out the improvement in the speaking skills.Based on the results of the analysis conducted by the researcher, it was found that the improvement in speaking skills in the first cycle reached classical completeness by 83% or 15 students who were complete. So that in the first cycle has reached the classical completeness of 75%.